2021
DOI: 10.1021/acs.biomac.1c00354
|View full text |Cite
|
Sign up to set email alerts
|

Toward Fabrication of Bioactive Papers: Covalent Immobilization of Peptides and Proteins

Abstract: Herein, we report a novel two-step method for the covalent, site-directed, and efficient immobilization of proteins on lab-made paper sheets. First, paper fibers were modified with a peptidic anchor comprising enzyme recognition motifs. Four different conjugation strategies for peptide immobilization were evaluated with respect to reproducibility and fiber loading efficiency. After manufacturing of the peptide-preconditioned paper, oriented conjugation of the model protein tGFP containing a C-terminal recognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…102 Liebich et al explored four different peptide conjugation strategies and evaluated two conjugation enzymes (sortase A and microbial transglutaminase) for directed target protein coupling. 102 Another important consideration for protein immobilization on paper substrate is retarding its specificity and immunological activity to overcome the detection limit. It can highly affect the device's performance if electron transfer is not guaranteed or if the protein undergoes major conformational changes that alter its functionality.…”
Section: Fabrication Of Paper Substrates With Biorecognition Elementsmentioning
confidence: 99%
See 2 more Smart Citations
“…102 Liebich et al explored four different peptide conjugation strategies and evaluated two conjugation enzymes (sortase A and microbial transglutaminase) for directed target protein coupling. 102 Another important consideration for protein immobilization on paper substrate is retarding its specificity and immunological activity to overcome the detection limit. It can highly affect the device's performance if electron transfer is not guaranteed or if the protein undergoes major conformational changes that alter its functionality.…”
Section: Fabrication Of Paper Substrates With Biorecognition Elementsmentioning
confidence: 99%
“…116 Liebich et al reevaluated four different peptide conjugation strategies for functional protein immobilization on paper, and two conjugation enzymes, sortase A and microbial transglutaminase, are used for directed target protein coupling. Their work showed a relatively comprehensive view for protein immobilization strategies evaluation and could be devoted to achieve high protein loads using biofunctionalized papers 102 (Fig. 3D).…”
Section: Fabrication Of Paper Substrates With Biorecognition Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical adsorption is performed by establishing a covalent bond between the functional groups present in the receptor structure (i.e., those that do not interact with the analyte) and the active sites at the substrate surface [168]. The surface of the paper is modified by organic polar solvents, such as ethanol [169].…”
Section: Classification Of Bio-ppoct Based On Immobilization State Of Bioreceptorsmentioning
confidence: 99%
“…10 Owing to its strong ligation capacity, various studies have revealed the potential of MTG for preparing hybrid materials that consist of a protein and various compounds and materials such as small molecules, 11 drugs, 12 lipids, 13 peptides, 14 DNA, 15 RNA, 16 proteins, 17 synthetic polymers, 18 and paper sheets. 19 Although Patzsch et al have investigated MTG activity in solutions of glycerol, 20 the catalytic behavior of MTG in crowded conditions remains unclear.…”
Section: Introductionmentioning
confidence: 99%